Green Workforce Transition Competencies in Education and Health: Policy Strategies to Support Sustainable Economic Investments In Bekasi - Utomo, Kurniawan Prambudi; Dira, Aldi Friyatna; Abdulrahman, Abdulrahman; Winardi N, Muhammad Aziz (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2025)
This study aims to analyze the effect of green labor relations in the education and health sectors on sustainable economic investment, green labor reflects the important role of human resources in encouraging environmentally friendly practices in society, which has a direct impact on economic sustainability. The research method involves collecting primary data through a survey of 200 workers as respondents in the education and health sectors. The data was processed using SPSS to test validity, reliability, and correlation between variables. The study was conducted for four months from July - October 2024. Furthermore, SEM was used to test the causal relationship between green labor, sustainable economic investment, and mediating variables such as education quality and health. The results of the analysis show that green labor has a significant influence on sustainable economic investment. The quality of education and health factors act as mediators that strengthen this relationship. The SEM model shows that a good fit index of the CFA model in the study has been met, while the RMSEA value in the study can be accepted, indicating that the research model can explain the relationship between variables adequately. This finding emphasizes the importance of green workforce development to support investment policies that are oriented towards inclusive and environmentally friendly economic growth, to encourage sustainable economic investment. Keywords : Green Workforce; Sustainable Investment; Education Quality; Health Services; Sustainable Economy